2018
DOI: 10.1111/echo.13801
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between cardiac magnetic resonance T2* and left ventricular global longitudinal strain in people with β‐thalassemia

Abstract: The participants with cardiac iron overload had a lower GLS than those without one. This suggests that GLS may be a useful method to predict myocardial iron overload particularly in β-thalassemia patients with subclinical cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
4
16
1
1
Order By: Relevance
“…Monte et al [22] and Li et al [23] found no correlation between left ventricular deformational parameters and T2* signals. Our study is in agreement with others [24,25], where they found a correlation of longitudinal strain with the T2* signal. It is noteworthy that in our study, iron-overloaded patients had similar LVEFs compared to non-iron-overloaded patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Monte et al [22] and Li et al [23] found no correlation between left ventricular deformational parameters and T2* signals. Our study is in agreement with others [24,25], where they found a correlation of longitudinal strain with the T2* signal. It is noteworthy that in our study, iron-overloaded patients had similar LVEFs compared to non-iron-overloaded patients.…”
Section: Discussionsupporting
confidence: 94%
“…Chronic tissue hypoxia in addition to chronic anemia, nutritional deficiencies and viral infections may contribute to the different susceptibilities to iron overload and cardiac damage. Moreover, myocardial fibrosis has been revealed in CMR studies in both iron-and non-iron-overload patients [32]: longlasting consequences of previous damage could explain the contradictory results on the correlation between the actual CMR T2* signal and left ventricular deformational parameters [22][23][24][25]32]. Our results demonstrated a significant correlation between liver and heart iron load assessed by MRI-T2*, while this correlation was lost at follow-up.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The GLS is altered despite preserved LV function, as assessed by the ejection fraction and seems to be helpful in the prediction of cardiovascular outcomes in the general population 13 . These methods have already been evaluated specifically in patients with β-thalassemia, demonstrating an important correlation even with cardiac damage secondary to iron overload 14 . They also present a better prognostic value for diastolic dysfunction in this group of patients than parameters evaluated in traditional echocardiography 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes resulting from activation of NF-Kβ transcription factor in the downstream of this pathway, increase the expression of VCAM, MCP-1, VEGF and MMP molecules on the ECs surface. Increased expression of these molecules reduces endothelium-dependent vasodilation, which can impair ECs structure and affects CVD development [ 69 71 ]. MCP-1/ICAM-1 molecules, which are expressed by increasing ROS production and subsequent epigenetic changes are associated with NF-Kβ signaling on ECs surface; they can alter ECs structure by increasing monocyte-endothelial adhesion, and subsequently induce atherosclerosis and other CVDs [ 72 , 73 ].…”
Section: The Role Of Exosome In Oxidative Stress Inductionmentioning
confidence: 99%